SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL ACTIVITIESSTUDY OF SOME AZO DERIVATIEVES OF AMINOTHIADIAZOLEDERIVED FROM NICOTINIC AND ISONICOTINIC ACIDS - Tomi, Ivan; Al-Daraji, Ali; Al-Qaysi, Raya; Hasson, Mohammed; Al-Dulaimy, Khlood (Iraqi Journal of Science, 2024)
In this study we synthesized the new compounds containing bis-1,3,4-thiadiazole3(A-D)n through many eaction steps (cyclization, diazotiazation and etherificationrespectively). The compounds have been characterized by melting point, FTIR and1HNMR data. All the synthesized compounds have been evaluated in vitro for theirantimicrobial activities against several microbes like: Escherichia coli, Klebsielliapneumonia, Pseudomonas aerugenosa, Serratia marscens and Staphylococcus aureusand the results showed that some of these compounds have very good antibacterialactivity.